A Novel Approach on Microwave Hyperthermia - Altintas, Gulsah; Akduman, Ibrahim; Janjic, Aleksandar; Yilmaz, Tuba (MDPI AG, 2021)
Microwave hyperthermia (MH) requires the selective focusing of microwave energy on the targeted region while minimally affecting the healthy tissue. Emerging from the simple nature of the linear antenna arrays, this work demonstrates focusing maps as an application guide for MH focusing by adjusting the antenna phase values. The focusing of the heating potential (HP) on different density breast models is performed via the proposed method using Vivaldi antennas. The effect of the tumor conductivity on the focusing is discussed. As a straightforward approach and utilizing the Vivaldi antennas, the system can be further combined with MH monitoring application.
Keywords: focusing; Medicine (General); R5-920; microwave hyperthermia; breast hyperthermia; microwave hyperthermia; focusing; breast hyperthermia; Article